Physiology or angiography-guided coronary artery bypass grafting: a meta-analysis - Martins, José (2022)
Background: While invasive coronary angiography is considered the gold standard for the diagnosis of coronary artery disease (CAD) involving the epicardial coronary vessels, coronary physiology-guided revascularization represents a contemporary gold-standard practice for the invasive management of patients with intermediate CAD. Nevertheless, the long-term results of assessing the severity of stenosis through physiology compared to the angiogram as the guide to bypass surgery – coronary artery bypass grafting (CABG) are still uncertain. This metaanalysis aims to assess the clinical outcomes of a physiology guided CABG compared to the angiography-guided CABG. Objectives: We sought to determine if outcomes differ between a physiology guided CABG compared to an angiography-guided CABG. Methods: We searched Medline, EMBASE, and the Cochrane Library. The last date for this search was June 2020, and all of the previous studies were included. We conducted a pooled risk-ratio meta-analysis for four main outcomes: all-cause death, myocardial infarction (MI), target vessel revascularization (TVR) and major adverse cardiovascular events (MACE). P-value <0.05 was considered as statistically significant. Heterogeneity was assessed with Cochran’s Q test and quantified by the I2 index. Results: We identified five studies that included a total of 1,114 patients. A pooled meta-analysis showed no significant difference between a physiology guided strategy and an angiography-guided strategy in MI (risk ratio [RR] = 0.72; 95%CI, 0.39–1.33; I2 = 0%; p = 0.65), TVR (RR = 1.25; 95%CI = 0.73–2.13; I2 = 0%; p = 0.52), or MACE (RR = 0.81; 95%CI = 0.62–1.07; I2 = 0%; p = 1). The physiology guided strategy has 0.63 times the risk of all-cause death compared to the angiography-guided strategy (RR = 0.63; 95%CI = 0.42–0.96; I2 = 0%; p = 0.55). Conclusion: This meta-analysis demonstrated a reduction in all-cause death when a physiology guided CABG strategy was used. Nevertheless, the short follow-up period, small sample size of the included studies and the non-discrimination of the causes of death can largely justify these conclusions. Studies with an extended follow-up period of observation are required to draw more robust and definitive conclusions.